ANALISIS YURIDIS TERHADAP SISTEM PEMBUKTIAN PADA KEJAHATAN PERETASAN SITUS WEBSITE - Ardiansyah, Ardiansyah; Deliana, Evi; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The crime of website hacking is already a widespread crime in Indonesia. Crime of website hacking is a type of crime that is difficult to detect. Unlike ordinary conventional crimes, crime victims generally do not realize that they have become victims, they generally do not report because they think that the existing law has not ensnared the perpetrators, the lack of knowledge of the legal apparatus regarding technological developments so that they are less able to anticipate the development of these crimes, also because they assume proving that a crime has occurred in front of the court is very difficult. The perpetrators of hacking website hacking there are charged with the applicable law, even though in reality there is no specific article governing the crime of hacking on the website. There should be a more specific regulation regarding the evidence system for hacking website mebsite crime because Indonesia is a country that adheres to the principle of legality, if a crime occurs then it will be seen whether there are legal provisions that govern it and whether the existing rules can be enforced. Based on this understanding, the authors identify two problem formulations, First how the type of modus operandi in website hacking crimes is rife in Indonesia. Second, how is the weakness of the evidentiary system in the crime of hacking websites in Indonesia.This type of research can be classified in normative juridical research, because this research is conducted by examining secondary data and approaches to law, this normative research examines the principles of legal principles of law. The data sources used are, primary data, secondary data, tertiary data, data collection techniques in this study are normative juridical, the data used is library research.Based on the results of research and problems in this study is the modus operandi of the crimes of hackers that is to find the target computer system that is about to be entered, then infiltrate and tap the password, and the last is exploring the computer system. Weaknesses in the system of proving hacking websites can be seen from the legal instruments which are one of the obstacles in proving the crime. This can be felt as if the crimes committed by law enforcers are not ready or even unable (technological stuttering) to investigate the perpetrators and the evidence used in connection with this form of crime is difficult to detect. In general, investigators are still very minimal in mastering computer operations and understanding of computers as well as the ability to conduct investigations of these cases.Keywords: Cyber Crime, Proof System, Website Hacking Website